4x-2*(60)+2x-(60)=180

Simple and best practice solution for 4x-2*(60)+2x-(60)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2*(60)+2x-(60)=180 equation:


Simplifying
4x + -2(60) + 2x + -1(60) = 180

Multiply -2 * 60
4x + -120 + 2x + -1(60) = 180

Multiply -1 * 60
4x + -120 + 2x + -60 = 180

Reorder the terms:
-120 + -60 + 4x + 2x = 180

Combine like terms: -120 + -60 = -180
-180 + 4x + 2x = 180

Combine like terms: 4x + 2x = 6x
-180 + 6x = 180

Solving
-180 + 6x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '180' to each side of the equation.
-180 + 180 + 6x = 180 + 180

Combine like terms: -180 + 180 = 0
0 + 6x = 180 + 180
6x = 180 + 180

Combine like terms: 180 + 180 = 360
6x = 360

Divide each side by '6'.
x = 60

Simplifying
x = 60

See similar equations:

| 0=(z-3)(z-3)(z-3) | | 5p+3=14 | | (x-6)(x-4)=-16 | | 4x-2*(-60)+2x-(-60)=180 | | 0=[(2m+7)-n][(2m+7)-n] | | 0=9/16y-63 | | 4*0-2y+2*0-y=180 | | x^2+4x+y^2+6y=-13 | | 0=[(9r-s)+2][(9r-s)-2] | | 4*(30+0.5y)-2y+2*(30+0.5y)-y=180 | | n=4(3+2) | | 0=[(4y-1)+z][(4y-1)+z] | | 2.44-3.1t=21.05 | | 80t=720 | | 90t=720 | | 0=(2z^4-3y)(2z^4-3y) | | 36+0+4*36-2*0+2*36-0= | | 5ln(6x)=40 | | 3/5x-4/7y-2x+5/7y | | 0=(a-6b)(a-6b) | | 4x+8+6x-5=33 | | x+0+4x-2*0=180 | | 13+3p+10=23+3p | | 36+0.2y+4*(36+0.2y)-2y=180 | | 5(2c+7)-3c=7(c+5) | | 7+4y=39 | | 3x+7=9x+1 | | 2m-(5m-4)=7+(-m+2) | | x/4+9=15 | | 7n+3=2n+23 | | 521/2+4 | | 0=(2m^3+n)(2m^3-n) |

Equations solver categories